Probiotics for the prevention of mortality and sepsis in preterm very low birth weight neonates from low- and middle-income countries: a Bayesian network meta-analysis - Thomas, Deena; Sharma, Akash; Sankar, M. Jeeva (Frontiers in Nutrition, 2023)
Background: Probiotics have been shown to reduce the risk of mortality and necrotizing enterocolitis (NEC) in very low birth weight (VLBW) neonates. The probiotic species with the maximal benefits in neonates from low- and middle-income countries are unknown. Objective: To identify the strain of probiotics with the maximum benefit in preventing neonatal mortality, sepsis, and NEC using the bayesian network meta-analysis. Search methods: We searched Medline via PubMed, Embase, and Cochrane Central Register of Controlled Trials (CENTRAL). We also hand-searched reference lists of previous systematic reviews to identify eligible studies. Selection criteria: Randomized controlled trials (RCTs) from LMICs comparing enteral supplementation of one or more probiotics with another probiotic species or placebo were included. Data collection and analysis: Two authors screened the studies, extracted the data, and examined the risk of bias using the Cochrane risk of bias 2 (RoB 2) tools. Bayesian network meta-analysis was performed using the “BUGSnet” package in R and RStudio (version 1.4.1103). The confidence in the findings was assessed using the Confidence in Network Meta-analysis (CINeMA) web application. Results: Twenty-nine RCTs enrolling 4906 neonates and evaluating 24 probiotics were included. Only 11 (38%) studies had a low risk of bias. All the studies compared the probiotics with placebo and not between different probiotic species; almost all probiotics were evaluated in only one trial. When compared to the placebo, the combination of B longum, B bifidum, B infantis, and L acidophilus may reduce the risk of mortality (relative risk [RR] 0.26; 95% credible interval [CrI] 0.07 to 0.72), sepsis (RR 0.47; 95% CrI 0.25 to 0.83), and NEC (RR 0.31; 95% CrI 0.10 to 0.78) but the evidence was very uncertain. There is low certainty evidence that the single probiotic species, B lactis, could reduce the risk of mortality (RR 0.21; 0.05 to 0.66) and NEC (RR 0.09; 0.01 to 0.32). Conclusion: Given the low to very low certainty of evidence for the efficacy of the two probiotics found to reduce mortality and necrotizing enterocolitis, no firm conclusions can be made on the optimal probiotics to be used in preterm neonates in low- and middle-income countries.